2014
DOI: 10.1038/srep06688
|View full text |Cite
|
Sign up to set email alerts
|

A human CCT5 gene mutation causing distal neuropathy impairs hexadecamer assembly in an archaeal model

Abstract: Chaperonins mediate protein folding in a cavity formed by multisubunit rings. The human CCT has eight non-identical subunits and the His147Arg mutation in one subunit, CCT5, causes neuropathy. Knowledge is scarce on the impact of this and other mutations upon the chaperone's structure and functions. To make progress, experimental models must be developed. We used an archaeal mutant homolog and demonstrated that the His147Arg mutant has impaired oligomeric assembly, ATPase activity, and defective protein homeos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 39 publications
4
34
0
Order By: Relevance
“…Here, one key player is chaperonin containing TCP-1 (CCT, also known as TRiC or group II chaperonin), a cytosolic ATP-dependent eukaryotic chaperonin comprising two rings of eight different but related subunits, each thought to be represented once per eight-membered ring. Autosomal recessive mutations of the CCT5 and CCT4 subunits lead to loss-of function phenotypes that manifest with a devastating sensory neuropathy45. Moreover, recent studies suggested that mRNA levels of the TRiC complex are repressed in Alzheimer's disease patient brain samples6.…”
mentioning
confidence: 99%
“…Here, one key player is chaperonin containing TCP-1 (CCT, also known as TRiC or group II chaperonin), a cytosolic ATP-dependent eukaryotic chaperonin comprising two rings of eight different but related subunits, each thought to be represented once per eight-membered ring. Autosomal recessive mutations of the CCT5 and CCT4 subunits lead to loss-of function phenotypes that manifest with a devastating sensory neuropathy45. Moreover, recent studies suggested that mRNA levels of the TRiC complex are repressed in Alzheimer's disease patient brain samples6.…”
mentioning
confidence: 99%
“…Archaea have not been used as models to specifically study molecular aspects of human chaperonopathies until very recently (Min et al, 2014). However, studies on the structure and properties of the thermosome, the archaeal equivalent of the human CCT, have been going on for nearly 30 years.…”
Section: An Archaeal Experimental Modelmentioning
confidence: 99%
“…In the wild type CCT5 the amino acid His is at this position but in the pathogenic mutant His is replaced by Arg. We found by a series of alignments and 3D modeling studies that position 138 in Pf-Cpn is equivalent to the 147 position in human CCT5 and it is occupied by Ile (Figure 5; information on the primary and secondary structures is available in Min et al, 2014). To examine the impact of the mutations we used Pf-CD1, which is the recombinant molecule Pf-Cpn lacking the last 22 amino acids that are involved in extreme heat resistance and have no match in the human CCTs.…”
Section: The Thermosome Of Pyrococcus Furiosusmentioning
confidence: 99%
See 2 more Smart Citations